COMPETENTNCE AND VALUE APPROACHES AT HIGHER SCHOOL - Vasyl H. Romaniuk; Liudmyla V. Romaniuk (Інформаційні технології і засоби навчання, 2010)
The publication opens unity of competence's and value's approaches in university education as bases of pedagogical process in modern conditions, which should include mutual assistance of all of its participants.